A case study of local ecological knowledge of shellfishers about edible cockle (Cerastoderma edule) in the Ria de Aveiro lagoon, Western Iberia - Heitor O. Braga; Ulisses M. Azeiteiro; Luísa Magalhães (BMC, 2022)
Abstract Background The cockle is available to numerous fishing villages in Europe, especially Portugal. In the Ria de Aveiro, there is a lack of a fisheries management program and the need for new ecological studies on cockle biology, ecology, and conservation. We shared local ecological knowledge (LEK) highlights about the cockle-Cerastoderma edule (Linnaeus 1758) in the Ria de Aveiro in favor of adaptive management of this bioresource. Methods Semi-structured interviews with sixty shellfishers in this coastal lagoon were carried out during April and May 2021. LEK data on the biology and ecology of the cockle were analyzed using an ethical-emic approach and the model of integration of different individual skills. These informal data were compared with previously published data for the species, the Fish Base, and GBIF databases. Results and discussion The average minimum size of the cockle for capture was 23.4 mm, and the average capture per tide was 137.12 kg. The areas with the highest productivity and the most shellfish were RIAV1 and RIAV2. Cockles inhabit areas of sand and mud at an average depth of 2.71 cm. Feeds are mainly small particles, plankton, mud, and algae. The main predators were crabs, European plaice, and bird species. Cockles spawn primarily in late spring and summer. As of 2010, there was a slight decrease in cockle stocks in the Ria de Aveiro due to overfishing, increased rainfall, and changes in the sediment. Considering and analyzing this knowledge is essential for a better understanding of the environmental context the cockles thrive in the view of users of the natural resource. Conclusion Informal data shared by shellfishers in the Ria de Aveiro were typical of filter-feeding bivalves. LEK may assist in planning future management plans for cockles, and unrefuted data may serve as untestable hypotheses. Ethnobiological studies in the Ria de Aveiro lagoon with other species may improve the management of this system since multiple fisheries are carried out in this coastal area.